eSwine Farming: A QR Code-Driven Monitoring System for Improve Efficiency and Profitability - Glenda Binay; Chelsey Anongos; Ma. Angela Manayon; Jake Robles (Universidade Estadual de Alagoas, 2024)
As technology advances, many traditional activities are at risk of being lost, including the practice of swine farming. Swine farming is an ancient practice that dates back to 4900 BC, but its effectiveness may decrease as individuals increasingly rely on newer technological solutions. However, with the advent of QR codes, swine farming has taken on a new dimension, enabling farmers to collect real-time data on swine growth, health, and production. This study is specifically designed to improve the efficiency and profitability of swine farming, empowering farmers with accurate and timely information on the status of their swine. The system allows farmers to collect data quickly and easily on individual pigs, which can then be analyzed to identify any issues. This information can be used to help farmers make informed decisions about how to manage their swine farming operations, expand into new and more effective practices, and increase profitability. The eSwine system is a significant innovation in swine farming technology, providing a functional, usable, and reliable tool for farmers to manage their operations more effectively. With an average weighted mean of 3.65, eSwine is an essential asset for any farmer looking to maximize their profits while maintaining the health and welfare of their swine.